DIVERSITAS SERANGGA PADA PERKEBUNAN PEPAYA (Carica papaya L.) DI DAERAH SANUR, DENPASAR, BALI - Suartini, Ni Made; Sudatri, Ni Wayan; Watiniasih, Ni Luh (Metamorfosa: Journal of Biological Sciences; Vol 2 No 2 (2015), 2015)
The role of insects in papaya plants is as pollinators, pests, parasites and predators of other insects. Referring to the role of insects, this research was conducted to determine the insects on an papaya plantations. Traping method using methyl eugenol and ripe papaya fruit as well as the manual method with insect net used in this research. Each method was repeated three times with an interval of sampling is one week. Insect netting done on the same day with traping method. Samples were preserved and then taken to the laboratory for identification. Environmental factors were measured are: temperature, humidity, latitude and altitude. Insects were identified by reference: Borror et al . (1992), CSIRO I & II (1991) and also Peggie and Amir (2006). Five species belonging to the genus Bactrocera found on methyl eugenol traps and five species belonging to the genus Drosophila was found in ripe papaya fruit traps as well as 16 other species found using insect netting around the papaya plant. In addition, there is also the genus Paracoccus on a papaya plant. Bactrocera papayae and genus Paracoccus is an insect pest on papaya plants. Keywords: diversity, insect, papaya plantation, Sanur
Keywords: diversity, insect, papaya plantation, Sanur